Serological monitoring of a Toxoplasma infection after hematopoietic stem cell transplantation - Rossi, Cláudio L.; Nascimento, Fernanda S.; Barros-Mazon, Sílvia de; Dias, Daniela F.; Vigorito, Antonio C.; Souza, Cármino A. de (Revista do Instituto de Medicina Tropical de São Paulo, 2010)
We report a primary response to Toxoplasma gondii following a hematopoietic stem cell transplantation in a patient with multiple myeloma. The primary response to T. gondii was supported by IgM, IgG and IgA seroconversion. The patient was promptly treated and there were no complications related to toxoplasmosis in the subsequent months.